Stelis kolomeitsevae (Orchidaceae: Pleurothallidinae): a new species from Pichincha province, Ecuador - Koval, Vladimir A.; Karremans, Adam P. (Phytotaxa, 2025)
Stelis kolomeitsevae, a new orchid species from the cloud forests of Mindo, Pichincha Province, Ecuador, is described and illustrated. The species belongs to Stelis subgenus Stelis and is morphologically similar to Stelis lancea, from which it differs by its shorter leaves (4.0–6.5 cm vs. 6.0–10.0 cm), shorter petiole (0.5–1.0 cm vs. 1.5–2.0 cm), inflorescence up to three times longer than the leaf (vs. barely surpassing the leaf), smaller sepals (1.5–1.7 × 1.2–1.4 vs. 2.0–2.5 × 2.0) and shorter column (0.6 vs. 1.0 mm) with a 5-lobed clinandrium (vs. 3-lobed). Additionally, it is compared with other Ecuadorian species in the same complex, S. loejtnantii, S. protracta, and S. scitula, from which it is distinguished by smaller, narrow ovate leaves, shorter ramicauls, and distinct floral features, including a transversely hemispherical lip with an emarginate apex and a triangular callus along the dorsal middle. A digital composite plate of the taxonomic novelty, a distribution map of the new species and SEM photographs of details of the flowers are provided.